Beyond expectations: autonomy and the Iranian postgraduate students in Malaysian public universities - Neissi, Sina; Hussin, Habsah (Australian International Academic Centre, 2017)
Iranian learners at all levels of education (primary, secondary and tertiary) face a number of constraints in their studies due to restriction of educational system, cultures, upbringing and expectations of society. Based on this premise the researchers would like to explore the degrees of autonomy as practiced by selected Iranian postgraduate students studying at three premier public universities in Malaysia. Data were gathered using the Learner Autonomy Profile (LAP) developed by Confessore & Confessore (1992). The findings reveal that these Iranian postgraduate students do practice autonomy and know how to apply positive coping strategies in their studies; thus indicating positive contradiction from the normal expectations of Iranian learners’ performance in relation to autonomy. The paper concludes with the impacts and implications of the findings.